2002
DOI: 10.1002/1521-3773(20021115)41:22<4239::aid-anie4239>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Giant Amphiphiles by Cofactor Reconstitution

Abstract: Controlled modification of horseradish peroxidase with an apolar polymer chain (see figure) by cofactor reconstitution leads to giant amphiphiles, which form vesicular aggregates in aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(111 citation statements)
references
References 1 publication
0
111
0
Order By: Relevance
“…Whether the membrane has a mono-or a bilayered structure, and whether the PEG and HRP are segregated or mixed in the corona, is not yet known. The enzyme-polymer hybrid vesicles were further investigated according to their enzymatic activity [95,96]. The enzymatic activity decreased for HRP and the stability of the oxy complex was reduced for Mb.…”
Section: Formation Of Polymersomes From Polymers Comprising Biofunctimentioning
confidence: 99%
“…Whether the membrane has a mono-or a bilayered structure, and whether the PEG and HRP are segregated or mixed in the corona, is not yet known. The enzyme-polymer hybrid vesicles were further investigated according to their enzymatic activity [95,96]. The enzymatic activity decreased for HRP and the stability of the oxy complex was reduced for Mb.…”
Section: Formation Of Polymersomes From Polymers Comprising Biofunctimentioning
confidence: 99%
“…Boerakker et al have developed such a biohybrid amphiphile by reconstituting apo-horseradish peroxidase (apo-HRP) with its cofactor, ferriprotoporphyrin IX, carrying a polystyrene tail (Figure 24a and b). 230 In water, the enzymepolymer hybrid formed vesicular aggregates with diameters of 80-400 nm (Figure 24c).…”
Section: Polymersomes As Nanoreactorsmentioning
confidence: 99%
“…230 Velonia et al have constructed another type of biohybrid amphiphile by specific attachment of a polystyrene block to a reduced disulfide bridge of CAL B, exposed on the outer surface of the enzyme. 254 TEM studies of aqueous dispersions of PS-CAL B giant amphiphiles revealed the presence of micrometer long fibers that were built up from bundles of micellar rods.…”
Section: Polymer Micelles As Nanoreactorsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26] Examples include polymer conjugation via: co-factor reconstitution, 16 the biotin-streptavidin complex, 18 supramolecular complexation with cucurbituril, 19 charge-charge 20 and metal affinity 21,24 interactions, as well as lectin-mediated complexation. 25,27,28 The advantage of noncovalent systems is that temporal control of conjugate assembly and disassembly can be asserted by the presence of competitor molecules.…”
Section: Introductionmentioning
confidence: 99%